2021
DOI: 10.1097/corr.0000000000002009
|View full text |Cite
|
Sign up to set email alerts
|

CORR Insights®: Do We Need to Stabilize All Reduced Metaphyseal Both-bone Forearm Fractures in Children with K-wires?

Abstract: Where Are We Now? "D octor, does my child really need to go under anesthesia and have wires drilled into his bone?""Will fixing his wrist with wires make his arm perfect?" "We do not have a very good health insurance; how much is it going to cost to do surgery on him versus just putting him into a cast?"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In fact, because of the high risk that distal forearm fractures at the junction of the metaphysis and diaphysis will angulate in a cast, some authors recommend more aggressive initial surgical treatment with closed reduction, K-wire fixation, and casting [ 8 , 9 ]. One study demonstrated that when comparing distal radius and distal radius and ulna fractures treated with a long arm cast compared to a K-wire and a long arm cast, those treated without a K-wire sustained more displacements in the cast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, because of the high risk that distal forearm fractures at the junction of the metaphysis and diaphysis will angulate in a cast, some authors recommend more aggressive initial surgical treatment with closed reduction, K-wire fixation, and casting [ 8 , 9 ]. One study demonstrated that when comparing distal radius and distal radius and ulna fractures treated with a long arm cast compared to a K-wire and a long arm cast, those treated without a K-wire sustained more displacements in the cast.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that when comparing distal radius and distal radius and ulna fractures treated with a long arm cast compared to a K-wire and a long arm cast, those treated without a K-wire sustained more displacements in the cast. However, at a five-year follow-up, there were no differences between the two groups, and all fractures were eventually remodeled [ 8 ]. Pollen [ 2 ] also reported that young patients with open growth plates are able to correct the angulation deformity over time with fracture remodeling.…”
Section: Discussionmentioning
confidence: 99%